Sistema de control interno y su incidencia en los procesos presupuestarios en la gobernación de Manabí en el periodo 2016- 2017 - Macías Niemes, José Antonio (2019)
Public institutions in Ecuador are governed and regulated mainly by the Internal Control Standards issued by the General Comptroller of the State, where all the activities that must be developed for a correct use and destination of public resources are clarified. The internal control tool bases the operability within the public management, given the magnitude of funds that are managed and making the principles of transparency and access to public information prevail. The Governorate of Manabi is a public institution, characterized as the guiding and guiding entity of the National Government's policy in the Province, of the plans and projects promoted by the Ministry of the Interior at the provincial level. The purpose of this research is to examine the internal control system and its impact on the budget processes in the Governorate of Manabi in the period 2016 - 2017. The methodology developed in the research used the deductive method, through internal control matrices that show the level of compliance of the budget process, management indicators were applied that facilitated the measurement of efficiency and effectiveness in meeting goals and institutional objectives. Regarding the investigation techniques, observation, interview and documentary compilation were used, through which the source and sustainability information of the budgetary activities executed by the Governorate of Manabi was obtained. The results of the research indicate that the level of compliance with the annual programming is high. The generation of budget items is carried out correctly, with high confidence and low risk, reflecting the effective internal control exercised within the executed activities and, lastly, the management of the Governorate of Manabi was also analyzed through indicators of efficiency and effectiveness, it is evident that in 2017 these were more efficient and effective in the execution of the activities foreseen in the PAP. It is recommended to improve the weaknesses detected in the internal budget control. Keywords: Management, budget, control, operability, norms